2015
DOI: 10.1309/ajcp69rbnuhhojri
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations in Mucinous Lesions of the Uterus

Abstract: The results suggest a possible association between KRAS mutations and mucinous differentiation in endometrial carcinogenesis. KRAS status can help in assessing benign from precursor or malignant mucinous lesions as well as differentiate endometrial lesions from those of cervical origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Many studies correlated KRAS status with certain histopathological features; Xiong et al supported the role of KRAS mutations in the formation of superficial epithelial changes in endometrioid EC, which has been further associated with focal mucinous differentiation (37). A similar association between KRAS and mucinous differentiation was reported by He et al (38). Another interesting study by Steward et al identified KRAS mutations in 12 out of 42 endometriosis-associated endometrioid adenocarcinomas (39).…”
Section: Translation Of Kras Mutation Status Into Clinical Informatiosupporting
confidence: 77%
“…Many studies correlated KRAS status with certain histopathological features; Xiong et al supported the role of KRAS mutations in the formation of superficial epithelial changes in endometrioid EC, which has been further associated with focal mucinous differentiation (37). A similar association between KRAS and mucinous differentiation was reported by He et al (38). Another interesting study by Steward et al identified KRAS mutations in 12 out of 42 endometriosis-associated endometrioid adenocarcinomas (39).…”
Section: Translation Of Kras Mutation Status Into Clinical Informatiosupporting
confidence: 77%
“…In colorectal cancers, a KRAS mutation was detected in 35.6% of cases and is regarded as a useful predictive factor for the efficacy of anti‐epidermal growth factor receptor therapy (Van Cutsem et al, ). Furthermore, KRAS mutations were detected in various cancers at different frequencies, including thyroid gland cancer (Fukahori et al, ), biliary tract cancer (Kubicka et al, ), pulmonary adenocarcinoma (The Cancer Genome Atlas Research Network, ), testicular germ cell tumor (Litchfield et al, ), endometrial cancer (endometrioid carcinoma; Lax, Kendall, Tashiro, Slebos, & Hedrick, ; Zaino et al, ), mucinous adenocarcinoma (Alomari, Abi‐Raad, Buza, & Hui, ; He et al, ; Mackenzie et al, ; Yoo et al, ; Zaino et al, ), clear cell carcinoma (An, Logani, Isacson, & Ellenson, ; Zaino et al, ), ovarian cancer (low‐grade serous carcinoma), and serous borderline tumor (Boyd et al, ; Hunter et al, ; Jones et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KRAS mutations were detected in various cancers at different frequencies, including thyroid gland cancer (Fukahori et al, 2012), biliary tract cancer (Kubicka et al, 2001), pulmonary adenocarcinoma (The Cancer Genome Atlas Research Network, 2014), testicular germ cell tumor (Litchfield et al, 2015), endome- (Alomari, Abi-Raad, Buza, & Hui, 2014;He et al, 2015;Mackenzie et al, 2015;Yoo et al, 2012;Zaino et al, 2014), clear cell carcinoma (An, Logani, Isacson, & Ellenson, 2004;Zaino et al, 2014), ovarian cancer (low-grade serous carcinoma), and serous borderline tumor (Boyd et al, 2013;Hunter et al, 2015;Jones et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous, serous, clear cell, neuroendocrine, undifferentiated, and dedifferentiated carcinomas are classified as nonendometrioid ECs. 7,8 Among these, the refined definition of mucinous carcinoma is now specified as ECs with more than 50% of tumor cells containing intracytoplasmic mucin (Figure 2). 7,8 A subset of mucinous carcinomas, designated microglandular-like carcinoma due to its morphologic similarity to microglandular hyperplasia of the endocervical glands, is acknowledged by the WHO 2014 ( Figure 3).…”
Section: Advancements In Classification Ofmentioning
confidence: 99%
“…7,8 Among these, the refined definition of mucinous carcinoma is now specified as ECs with more than 50% of tumor cells containing intracytoplasmic mucin (Figure 2). 7,8 A subset of mucinous carcinomas, designated microglandular-like carcinoma due to its morphologic similarity to microglandular hyperplasia of the endocervical glands, is acknowledged by the WHO 2014 ( Figure 3). 9 Neuroendocrine tumors are now classified as low-grade neuroendocrine tumors (corresponding to carcinoids in previous classifications) and high-grade neuroendocrine carcinomas, encompassing small and large cell neuroendocrine carcinomas.…”
Section: Advancements In Classification Ofmentioning
confidence: 99%